The Doomsday argument, Adam & Eve, UN⁺⁺, and Quantum Joe - Bostrom, N (Kluwer Academic Publishers, 2001)
The Doomsday argument purports to show that the risk of the human species going extinct soon has been systematically underestimated. This argument has something in common with controversial forms of reasoning in other areas, including: game theoretic problems with imperfect recall, the methodology of cosmology, the epistomology of indexical belief, and the debate over so-called fine-tuning arguments for the design hypothesis. The common denominator is a certain premiss: the Self-Sampling Assumption. We present two strands of argument in favor of this assumption. Through a series of throught experiments we then investigate some bizarre prima facie consequences - backward causation, psychic powers, and an apparent conflict with the Principal Principle.